Pesantren, Nationalism And Integration - Ma'as Shobirin (Review of Islam in Southeast Asia, 2018)
Indonesian independence cannot be separated from the roleand contribution ofpesantren (Islamic boarding school).Pesantren alsohas a strong social baseandinfluenceinactualizingitsrolein building a sense of nationalism.In this section, the writer tries to describe the existence of pesantrenandits role in fighting for independence, the actualization of national valuesinpesantren, therole ofpesantren in fortifying NKRI (Unitary State of the Republic of Indonesia/ Negara Kesatuan Republik Indonesia), and theeffort ofpesantreninteaching the love to the homeland.This article is based on litherature analysis of pesantren. It argued that pesantren and its community have influenced shaping and developing Indonesian nationalism and integration, founding the moderate Islamism and preserving peaceful Islam. The challenge with pesantrens is the rise of radicalism and the expectation for students at pesantrens to compete in regional education and contributing in development.